Competition for FDI and Profit Shifting - Jie Ma; Pascalis Raimondos-Møller (Center for Economic Studies and ifo Institute (CESifo), 2015)
When countries compete for the location of a new multinational plant they need to be aware of the profit shifting opportunities this new plant creates for the global multinational firm. By modelling explicitly the multinational's intra-firm transactions, we show that the home market advantage that large countries have due to their size will be counteracted by such profit shifting opportunities. As a result of this, large countries will not be able to capitalize on their size and sustain high corporate taxes. We show that, on the basis of these profit shifting opportunities, a small country can easily win the location game ahead of a large country. How lenient the small country is in implementing transfer pricing regulations turns out to be an important variable in such location games.
Keywords: H25; F23; 330; profit shifting; competition for FDI; location game